Pengaruh TATO dan DER Terhadap ROA dengan Nilai Impor Bahan Baku Obat Sebagai Variabel Moderasi Pada Perusahaan Farmasi di Bursa Efek Indonesia Periode 2021-2025 - Leni Nuraeni; Nabilla Nurjannah; Nur Diansyah; Muhamad Nunu; Dinda Nurizka Putri; Erna Herlinawati (Ikatan Da'i Indonesia, 2026)
This study aims to examine and analyze the effect of Total Asset Turnover (TATO) and Debt to Equity Ratio (DER) on profitability, measured by Return on Assets (ROA), in pharmaceutical companies listed on the Indonesia Stock Exchange during the 2021–2025 period. Furthermore, this study incorporates Import as a moderating variable to determine its impact on these relationships. The analysis was conducted using panel data regression via EViews software. The results show that TATO has a positive and significant effect on ROA, indicating efficient asset utilization in generating profit. Conversely, DER has a negative and significant effect, reflecting the financial risk burdening corporate profitability. Moderation analysis proves that Import significantly strengthens the influence of TATO and DER on ROA. The Adjusted R-squared value of 0.7687 demonstrates that the model explains 76.87% of the variance in ROA, while the remainder is attributed to factors outside the model. These findings provide strategic implications for pharmaceutical financial managers in optimizing asset structures and debt policies amidst the volatility of raw material import reliance. This research underscores the importance of operational efficiency and funding risk management in enhancing corporate financial performance.